Recent Advances in Surface Characteristics of Dental Implants: A Mini Review - Pooja Mohanty1 , Manoj Kumar2 , Saurav Panda2 , Rinkee Mohanty3 , Rashmita Nayak4 , Anurag Satpathy4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Implants have become an integral part of dentistry today and are widely being used for the replacement ofmissing teeth. A considerable amount of advancements has come in Implant dentistry including the qualityof material, surface coatings and processes, and the surgical techniques as well. This review will deal withthe implant surface design and its characteristics which have been done till now to enhance the implant-bonecontact resulting in better osseointegration and subsequent long-term success of dental implants.